FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL PRANIKAH PADA SISWA SMA SAMARINDA - Sutrisno Sutrisno; Edi Purwanto; Rivan Firdaus (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2020)
Background; Adolescent Reproductive Health (15-24 years), 8% of young men agree to premarital sexual relations, and only 1% of young women. PKBI East Kalimantan (2008), among 300 adolescents (ages 13-20 years), 12% of respondents claimed to have had sex, 56% of them had sex like husband and wife, and most were high school / vocational high school students. Aim; The aim of this study was to determine the factors associated with premarital sexual behavior in high school students in Samarinda City. Research outputs can be: Modules, International Journals, Seminars, Flip sheets and Leaflets on Premarital Sexual Behavior in Adolescents, Method; The study used a cross sectional approach with a sample of 356 in 9 high schools and vocational schools in Samarinda, using the Slovin sample formula Results; 1) There is a significant relationship between attitude, religiosity, and parenting factors with premarital sexual behavior among high school students in the city of Samarinda. 2) There is no significant relationship between information source factors and premarital sexual behavior among high school students in Samarinda City. Conclusion; 1) It is very necessary to instill the values of good and positive attitudes for adolescents, especially in high school students as a reinforcement of premarital sexual understanding and its effects, 2) There needs to be an increase in fostering the appreciation and practice of religious values in schools and the implementation of religious obligations while at both at school and at home, 3) Open communication relations between parents and children are needed in order to implement good and democratic parenting.